Multidimensional materials and device architectures for future hybrid energy storage - Maria R. Lukatskaya (Nature Portfolio, 2016)
With the continued miniaturization of electronics, there are increasing efforts to engineer small, powerful energy storage devices. Here the authors review the cutting edge of this rapidly developing field, highlighting the most promising materials and architectures for our future energy storage requirements.